Modified MRC assessment and FEV1.0 can predict frequent acute exacerbation of COPD: An observational prospective cohort study at a single-center in Japan - Asai, Nobuhiro; Ohkuni, Yoshihiro; Ohashi, Wataru; Kaneko, Norihiro (Respiratory medicine, 2023)
Acute exacerbation (AE) of chronic obstructive pulmonary disease (COPD) is a fatal event, leading to poor outcomes among COPD patients. However, exact frequency and poor prognostic factors are not well known in Japan. and patients, To assess the frequency and risk factors of AE, we performed this prospective cohort study at the Kameda Medical Center in Japan between during 2011 and 2013. AE was defined as an acute worsening of respiratory symptoms according to the GOLD guideline. Furthermore, we compared the exacerbation-free time between the groups. A total of 330 patients (230 COPD patients and 100 smoking controls) were enrolled in the study. The mean age in the study was 73 years, and 94% of the patients were male. As for the frequency of AE, 0.17 times/patients/year was found in all patients. The frequency of AE increased as the COPD disease severity (p = 0.042 by Jonch-Heere terpla test). GOLD I patients had longer exacerbation-free time than GOLD II, and GOLD II grade COPD patients had longer exacerbation-free time than GOLD III grade COPD patients. In terms of risk factors for AE, logistic regression analysis showed that Modified Medical Research Council (mMRC) scale ≥3 and FEV <50% were independent poor prognostic factors for moderate grade of AE events, and mMRC scale ≥3 was independent poor prognostic factor for severe AE events. The frequency of AE increases as the disease severity becomes more severe. We found mMRC scale >3 and FEV1 <50% were risk factors for AE-COPD.